Chapter 16: Teaching sustainability: More than just a game - Watson, Rosina; Adams, Gemma; Borrelli, Rosina (Edward Elgar Publishing, 2024)
Achieving a sustainable future involves rethinking how we live, work, and do business, and understanding the steps people and organisations can take to drive these changes. This involves having a vision of what a just and sustainable future could look like, seeing business as part of an interconnected system, taking bold decisions and collaborating with others. The Exploring Sustainable Futures game is a role-playing learning experience that teaches these skills. Participants experience how the interrelated actions of businesses, government and citizens shape the future, in the context of four possible scenarios of a sustainable future by 2050. We outline how the design and delivery of the game teaches critical competencies for sustainability. We offer practical guidance on playing the game with management students and executive leadership teams. We present emerging evidence on the impact of game play on participants, and recommend more participatory methods for evaluating learning outcomes.
Keywords: Education; sustainability; serious game; systems thinking; collaboration; scenarios